Politeness of Vietnamese Students in Writing Request Email in English: a Course-based and Socio-pragmatic Study - Pham , Thi Minh Trang; Yeh, Aiden (International Journal of Language and Literary Studies, 2020)
This exploratory study investigates politeness strategies employed by Vietnamese EFL learners when writing English request emails sent to foreign and Vietnamese professors and school staff. A corpus-based critical discourse analysis is used to analyze sub-elements of politeness including the degree of imposition, terms of address, request-giving strategy and lexicon-syntactic modifier. The results support the assumption that Vietnamese language pragmatic knowledge is deeply ingrained and has tremendous influence on students’ L2 email writing skills. The study also reveals that Vietnamese students applied a high level of imposition with formal term of address and salutation, directness strategies with the overuse of “please” and other hedges. While gender is not a determining factor, the inflexible adoption of fixed phrases and syntactic-lexical devices were attributed to the lack of sociopragmatic competence. Thus, apart from linguistic knowledge, the role of cultural awareness and socio-pragmatic knowledge should be highlighted in communicative English learning and teaching.